The hidden danger: Silent celiac disease - Gönül Çaltepe (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Çaltepe G. The hidden danger: Silent celiac disease. Turk J Gastroenterol 2018; 29: 530-1.